Urban resilience assessment based on complex ecosystem theory: evidence from the Yangtze River Middle Reaches Urban Agglomeration - Wenziyi Li; Liting Xu; Yu Xu; Xinghua Feng; Dabao Zhou (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Dual-targeted nanophotosensitizer potentiates oral squamous cell carcinoma therapy through synergistic ROS induction and pyroptosis - Hongru Zhang; Jingyuan Wang; Yang Yu; Zidan Xu; Zeyu Zhang; Liting Zeng; Guanxiong Zhu; Lu Liang; Lingmin Zhang; Lina Yu (Chemical Engineering Journal, 2026)

Photoperiod induces alterations in redox homeostasis, immune response, and responses to light stimulation in the red swamp crayfish (Procambarus clarkii) - Lang Zhang; Qi Bai; Yingchun Mu; Yali Yu; Liting Ye; Lu Qiao; Wenya Ji; Jie Peng; Meiping Lan; Ziwei Song; Yu Fang (Aquaculture, 2026)

The “net-capturing” effect of bacteria on the transport of fibrous and fragmental microplastics in porous media: Revealed with the real-time pore-scale visualized and quantitative experiments - Shunan Dong; Jingjie Dong; Xiaoting Su; Qianhui Yu; Liting Sheng; Yuanyuan Sun; Jichun Wu (Journal of Hazardous Materials, 2026)

Immune dysregulation and cellular dysfunction mediate di-n-pentyl phthalate–induced hepatotoxicity: Insights from single-cell RNA sequencing - Yu Gan; Yongyi Luo; Xiandong Ye; Kaiyan Zhang; Zhenqiu Xia; Lei Yang; Chaoming Zhou; Gan Xie; Wenyan Zhong; Tengfei Yuan; Shuimiao Lin; Yuan Fang; et al. (Food and Chemical Toxicology, 2026)

Alisma plantago-aquatica tolerance and plant-microbe synergy in nitrogen removal under elevated ammonium stress - Shuang Wang; Jun Liu; Qiuyi Zhu; Yanchen Chen; Yu Cao; Jiale Gu; Ya Liu; Qilin Liu; LiTing Wang; Yan Lei; Longfei Jiang; Zhaocheng Wu (Process Safety and Environmental Protection, 2026)

Associations of serum per- and polyfluoroalkyl substances (PFAS) mixture with the risk of chronic diseases: evidence from single‑ , multi-pollutant, and machine learning models - Mei Li; Liting Sheng; Zige Ding; Guangsheng Yu; Yichu Chen; Qitian Chen; Wei Shao; Bingxin Liu; Mulong Du; Dongying Gu; Silu Chen; Junyi Xin; et al. (Archives of Toxicology, 2026)

Dual-responsive structural color smart labels for humidity monitoring - Tianyi Song; Liting Huang; Shaofeng Yuan; Hang Yu; Kunfeng Liu; Yahui Guo; Yuliang Cheng; Weirong Yao (Journal of Food Engineering, 2026)

Nitrogen Dominates Sedimentary Organic Carbon Distribution in a Tropical Marine Ranch - Xiaoran Shi; Liting Chen; Aiyao Yang; Yu Han; Xiaoju Pan; Zhaoyun Wang; Weijie Gong; Xiangen Wu (Journal of Marine Science and Engineering, 2026)
Marine ranching, as a pivotal strategy for enhancing the ocean’s carbon sequestration potential, offers significant potential to mitigate nearshore fishery depletion and restore marine ecosystems amid the global carbon neutrality agenda. However, the mechanistic pathways linking sediment total organic carbon (TOC) to various environmental factors in tropical marine ranches remain insufficiently quantified. This study selected the Wuzhizhou Island Marine Ranch in Hainan Province—a representative tropical marine ranch—as the research site. Field investigations and sampling were conducted during the dry (March 2024) and wet (September 2024) seasons to quantify TOC in surface sediments and associated environmental variables. A two-step analytical framework, integrating Principal Component Analysis (PCA) and Generalized Additive Models (GAM), was employed to elucidate the environmental drivers governing the spatiotemporal dynamics of TOC. The results show that the surface sediment TOC at Wuzhizhou Island Marine Ranch exhibits a distinct spatial gradient—Core Reef > Atoll > Control > Estuarine, and a pronounced seasonal pattern with elevated concentrations in the dry season relative to the wet season. The spatiotemporal differentiation of TOC is mainly driven by a gradient (explaining 52.1% of variation) that encompasses processes related to carbon accumulation from terrestrial inputs and primary production, as well as organic matter degradation promoted by nutrients and higher water temperatures. Sediment total nitrogen (TN) emerges as the primary environmental driver of TOC distribution, contributing up to 46.9% of the variance at an extremely significant level (p

Interactions of microbiota during solid-state cereal vinegar fermentation - Dantong Liu; Zhenhua Su; Qi Han; Liting Wang; Linna Tu; Yongjian Yu; Menglei Xia; Yanbing Shen; Yu Zheng; Min Wang (Trends in Food Science & Technology, 2026)

Research on PEMFC gas supply system: from structural improvement to advanced control strategies - Zhendong Yu; Ying Tian; Jiaqi Liu; Liting Wang (Fuel, 2026)

The humic acid-mediated mechanism of 6PPD-Q during transport process in porous media: Insights from column experiments and molecular dynamics simulations - Qianhui Yu; Shunan Dong; Jianyou Zhu; Genhe He; Jingjie Dong; Yanan Sun; Liting Sheng; Yuanyuan Sun; Jichun Wu (Environmental Pollution, 2026)

Experimental Study on Suppression and Mechanism of Sloshing Impact Pressure by Vertical Slat Screens Under Broadband Horizontal and Vertical Excitation - Liting Yu; Xiaoqian Luo; Jingcheng Lin; Jie Fan; Heng Jin (Journal of Marine Science and Engineering, 2026)
Sloshing-induced impact pressure is a key damage factor for marine liquid tanks. While research aimed at overcoming screen failure in sloshing suppression under high-frequency excitation has focused on wave height, the dataset of impact pressure remains lacking. Moreover, the pattern of pressure suppression under broadband excitation remains unclear. The primary contribution of this work is the first experimental dataset of impact pressure with vertical slat screens under broadband horizontal and vertical excitation. Second, it reveals pressure suppression patterns by screens across varying excitation frequencies and screen numbers. The results demonstrate that vertical slat screens can effectively suppress pressure. First, screen position matters more than number, proving that suppression is dominated by modal disturbance. Second, wave-height suppression does not reliably represent pressure suppression. Pressure suppression is systematically weaker. An exception occurs under vertical excitation, where pressure suppression can be stronger even when wave-height suppression fails. The results highlight the suppression mechanism dominated by modal disturbance and the instability inherent to parametric sloshing. Wave height, reflecting global potential energy, is effectively suppressed by modal disturbance. Pressure, originating from local kinetic energy, can be effectively suppressed by both modal disturbance and vortex dissipation.

Emissions of fully fluorinated greenhouse gases in central-eastern China inferred from atmospheric observations - Qianna Du; Xiaoyi Hu; Runze Zhu; Zifa Wang; Bowei Li; Liting Hu; Zhouxiang Cai; Mingrui Ji; Jingtao Xu; Haibo Yu; Yunxing Hu; Bo Yao; et al. (Journal of Environmental Management, 2026)

Molecular composition of water soluble fraction of petroleum products and crude oils: Insights into groundwater contamination potential and environmental forensics - Wang Yu; Yuruo Wan; Wei Zhou; Jiayi An; Liting Tian; Jie Ma (Journal of Environmental Sciences, 2026)

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)

The individual transport, cotransport and immobilization with solar pyrolysis biochar of microplastics and plasticizer in sandy soil - Shunan Dong; Yanan Sun; Xiyu Chen; Liting Sheng; Qianhui Yu; Wenyi Xie; Jihong Xia (Journal of Hazardous Materials, 2025)

Comparative metabolomics reveals biosignatures in wild vs. farmed Hypophthalmichthys nobilis: A UHPLC-MS/MS-based authentication strategy - Lang Zhang; Liting Ye; Ziwei Song; Yali Yu; Shaoqiang Wu; Qiuying Qin; Wenya Ji; Lekang Li; Wenwen Suo; Hui Zhang (Food Chemistry, 2025)

Fingerprinting complex mixed oil spills at refineries: Source identification, quantitative source apportionment, and biodegradation assessment - Wang Yu; Jiayi An; Jiuhao Song; Junjie Guan; Keyu Duan; Wei Zhou; Liting Tian; Jie Ma (Water Research, 2025)

The influence of homogenization–ultrasonic treatment on micro-nano particle characteristics, nutrient composition, flavor profile, and overall quality of Salmon head soup - Junli Feng; Ningsi Xu; Yiran Jin; Yu Zhang; Fei Xu; Fang Yao; Zejun Wang; Liting Ji; Qing Shen (Food Chemistry, 2025)

Elucidating the degradation mechanisms for capacity fading in cylindrical-type rechargeable alkaline Ni-Zn batteries - Liting Deng; Long Gu; Xian Li; Wencheng Su; Yuying Zhang; Jiajun Chen; Jianan Yu; Bin Wang; Chi-Wing Tsang; Chunzhen Yang (Chemical Engineering Journal, 2025)

Amino acid-induced supramolecular assembly defective carbon nitride for efficient photocatalytic CO2 reduction - Rui Li; Liting Lai; Si Li; Shipeng Wan; Wenbei Jia; Yu Han; Ruixuan Chu; Qin Zhong; Zhaoxiang Zhong (Chemical Engineering Journal, 2025)

Spatio-temporal evolution of rural industry and ecology based on perspective of symbiosis theory: Insights from Jiangxi Province, China - Dabao Zhou; Liting Xu; Wenziyi Li; Yu Xu; Xinghua Feng; Yu Fu; Yexi Zhong (Journal of Mountain Science, 2025)

Fabrication of lignin-containing cellulose nanofibers flocculant for ecological interception of phosphorous from farmland drainage - Yu Zhang; Yiyi Chen; Caizheng Cai; Caiyun Su; Haodong Hu; Liting Chen; Xinyuan Zhang; Jinsong He; Jinguang Hu; Fei Shen; Dong Tian (Chemical Engineering Journal, 2025)

Polyethylene microplastics impair chicken growth through gut microbiota-induced hepatic fatty acid metabolism dysfunction - Jiaping Xu; Qiuyue Zhang; Yu Wang; Zhipeng Cheng; Hongkai Zhu; Hongzhi Zhao; Yiming Yao; Liting Hua; Biting Qiao; Leicheng Zhao; Yongcheng Li; Lei Wang; et al. (Journal of Hazardous Materials, 2025)

Understanding water governance based on the social-ecological system framework integrating stakeholder perspective: A case study of aquaculture pollution governance in Taihu Lake, China - Liting Xu; Sophia Shuang Chen; Zheng Guo; Yuke Yuan; Yu Xu; Jiaqi Zhang (Environmental Impact Assessment Review, 2025)

Effects of Soil Components on Microplastics Transport and Retention in Natural Soils: Various Microplastics Types and Sizes - Weiya Fan; Shunan Dong; Xiyu Chen; Xiaoting Su; Qianhui Yu; Liting Sheng (Water, Air, & Soil Pollution, 2025)

Spatial differentiation and influencing factors of cropland abandonment: A case study in Chongyi county, Jiangxi Province, China - Yu Xu; Ying Huang; Liting Xu; Hualin Xie (Journal of Mountain Science, 2025)

Loading palladium clusters in porous organic cages for simultaneously enhancing H2 permeability and H2/CH4 selectivity of molecularly mixed composite membranes - Jia Pang; Haoyu Xu; Lu Qiao; Yao Wang; Liting Yu; Hongbin Wang; Caiyan Zhang; Hu Chang; Lili Fan; Rongming Wang; Zixi Kang; Daofeng Sun (Chemical Engineering Journal, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Resource utilization of tea waste in biochar and other areas: Current status, challenges and future prospects - Liting Hao; Ziheng Zhao; Hongliang Zhou; Litian Wen; Xiaofan Liu; Yang Yu; Ye Liu (Journal of Environmental Management, 2025)

Synthesis of value-added uridine 5'-diphosphate-glucose from sucrose applying an engineered sucrose synthase counteracts the activity-stability trade-off - Liting Zhao; Zhongbao Ma; Linpei Zhang; Yu Shen; Lei Chen; Youran Li; Sha Xu; Guiyang Shi; Daming Fan; Zhongyang Ding (Food Chemistry, 2025)

Cotransport of 6PPD-Q and pristine/aged microplastics in porous media: An insight based on transport forms and mechanisms - Qianhui Yu; Shunan Dong; Liting Sheng; Xiaoting Su; Lei Wang; Weiya Fan; Yulu Yu (Water Research, 2024)

Enhanced CO2 Reduction via S-Scheme Heterojunction of Amorphous/Crystalline Metal-free Carbon Nitride Photocatalysts - Liting Wu; Dingyi Yang; Yalin Dong; Ze Wang; Yu Zhang; Tingting Wang; Liang Cheng; Yong Wang; Yizhang Wu (Chemical Engineering Journal, 2024)

Insight into the differential response of functional denitrifiers to novel formulated organic amendments in soybean agroecosystem - Ugochi Uzoamaka Egbeagu; Yue Zhang; Yuanhang Wang; Ayodeji Bello; Liting Deng; Yu Sun; Yue Han; Liyan Zhao; Shuai Shi; Huajing Liu; Xiuhong Xu (Rhizosphere, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Large eddy simulation of the cavity shedding characteristics of ventilated cavitation around the underwater vehicle - An Yu; Liting Li; Daqing Zhou (Ocean Engineering, 2024)

Enhanced adsorption and cytotoxicity of hydrothermally aged microplastics for volatile organic compounds in sludge - Yang Yu; Ye Liu; Liting Hao; Bingxing Zhu; Xi Yang; Shifu Ge (Journal of Environmental Chemical Engineering, 2024)

Atlas and source of the microplastics of male reproductive system in human and mice - Wen Yang; Longmei Wu; Guanjian Li; Lan Shi; Junqiang Zhang; Liting Liu; Yuge Chen; Hui Yu; Kai Wang; Lei Xin; Dongdong Tang; Qunshan Shen; et al. (Environmental Science and Pollution Research, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Use of light-weight foaming polylactic acid as a lung-equivalent material in 3D printed phantoms - Scott Crowe; Sarah Maxwell; Harsimran Brar; Liting Yu; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2023)
The 3D printing of lung-equivalent phantoms using conventional polylactic acid (PLA) filaments requires the use of low in-fill printing densities, which can produce substantial density heterogeneities from the air gaps within the resulting prints. Light-weight foaming PLA filaments produce microscopic air bubbles when heated to 3D printing temperatures. In this study, the expansion of foaming PLA filament was characterised for two 3D printers with different nozzle diameters, in order to optimise the printing flow rates required to achieve a low density print when printed at 100% in-fill printing density, without noticeable internal air gaps. Effective densities as low as 0.28 g cm − 3 were shown to be achievable with only microscopic air gaps. Light-weight foaming PLA filaments are a cost-effective method for achieving homogeneous lung-equivalency in 3D printed phantoms for use in radiotherapy imaging and dosimetry, featuring smaller air gaps than required to achieve low densities with conventional PLA filaments.

Bioaugmentation treatment of coal chemical reverse osmosis concentrate in biological contact oxidation system coupled with ozone pretreatment - Xushen Han; Liting Huang; Yan Jin; Jianguo Yu (Journal of Cleaner Production, 2023)

Simvastatin-enhanced bioinspired exosome mimetics regulate osteogenesis and angiogenesis for the treatment of glucocorticoid-induced osteonecrosis of the femoral head - Hongyi Jiang; Chao Lou; Liting Jiang; Chihao Lin; Weidan Wang; Zijian Yan; Jiachen Yu; Tingwen Cai; Shida Lin; Jilong Wang; Xiaoyun Pan; Xinghe Xue (Chemical Engineering Journal, 2023)

A structure-based gamma evaluation method for identifying clinically relevant dose differences in organs at risk - Liting Yu; Anthony Baker; Tanya Kairn; Alexander Livingstone; Jamie Trapp; Scott B Crowe (Physical and Engineering Sciences in Medicine, 2023)
Gamma evaluation is currently the most widely used dose comparison method for patient specific quality assurance (PSQA). However, existing methods for normalising the dose difference, using either the dose at the global maximum dose point or at each local point, can respectively lead to under- and over-sensitivity to dose differences in organ-at-risk structures. This may be of concern for plan evaluation from clinical perspectives. This study has explored and proposed a new method called structural gamma, which takes structural dose tolerances into consideration while performing gamma analysis for PSQA. As a demonstration of the structural gamma method, a total of 78 retrospective plans on four treatment sites were re-calculated on an in-house Monte Carlo system and compared with doses calculated from the treatment planning system. Structural gamma evaluations were performed using both QUANTEC dose tolerances and radiation oncologist specified dose tolerances, then compared with conventional global and local gamma evaluations. Results demonstrated that structural gamma evaluation is especially sensitive to errors in structures with restrictive dose constraints. The structural gamma map provides both geometric and dosimetric information on PSQA results, allowing straightforward clinical interpretation. The proposed structure-based gamma method accounts for dose tolerances for specific anatomical structures. This method can provide a clinically useful method to assess and communicate PSQA results, offering radiation oncologists a more intuitive way of examining agreement in surrounding critical normal structures.

TabZIP60 is involved in the regulation of ABA synthesis-mediated salt tolerance through interacting with TaCDPK30 in wheat (Triticum aestivum L.) - Lina Zhang; Lijuan Zhao; Liting Wang; Xingyan Liu; Zhen Yu; Jing Liu; Wangze Wu; Lan Ding; Chuan Xia; Lichao Zhang; Xiuying Kong (Planta, 2023)

A new strategy for the enrichment of ammonia-oxidizing archaea in wastewater treatment systems: The positive role of quorum-sensing signaling molecules - Peihan Zheng; Qian Zhang; Jiaxing Zou; Qi Han; Jiarong Han; Qixin Wang; Liting Yao; Guangwei Yu; Yuhai Liang (Science of The Total Environment, 2023)

Effects of four hormones on the mitigation of ovarian damage in tilapia (Oreochromis niloticus) after copper and cadmium exposure - Yijie Wu; Ting Huang; Xin Yan; Jun Xiao; Zhirui Ma; Liming Luo; Liting Chen; Jinling Cao; Zhanyang Tang; Xinxian Wei; Fuyan Chen; Yu Zhu; et al. (Aquatic Toxicology, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Deciphering biochar compost co-application impact on microbial communities mediating carbon and nitrogen transformation across different stages of corn development - Ayodeji Bello; Wanying Liu; Nuo Chang; Kehinde Olajide Erinle; Liting Deng; Ugochi Uzoamaka Egbeagu; Busayo Joshua Babalola; Han Yue; Yu Sun; Zimin Wei; Xiuhong Xu (Environmental Research, 2023)

Seasonal variation in the nutritional components and textural properties of Pacific abalone and its hybrids - Wenchao Yu; Liting Zeng; Weiguang Zou; Ying Shu; Jin-Chywan Gwo; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Large eddy simulation of the pulsation characteristics in the cavitating flow around a NACA0015 hydrofoil - An Yu; Liting Li; Daqing Zhou; Jingjing Ji (Ocean Engineering, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Disentangling the coupling relationships between functional denitrifiers and nitrogen transformation during cattle-manure and biochar composting: A novel perspective - Liting Deng; Wanying Liu; Nuo Chang; Lei Sun; Jizhou Zhang; Ayodeji Bello; Ugochi Uzoamaka Egbeagu; Shuai Shi; Yu Sun; Xiuhong Xu (Bioresource Technology, 2023)

Comparative Methylome Analysis Reveals Epigenetic Signatures Associated with Growth and Shell Color in the Pacific Oyster, Crassostrea gigas - Chao Tan; Chenyu Shi; Yin Li; Wen Teng; Yongjing Li; Huiru Fu; Liting Ren; Hong Yu; Qi Li; Shikai Liu (Marine Biotechnology, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Dynamics of fungal species related to nitrogen transformation and their network patterns during cattle manure–corn straw with biochar composting - Ayodeji Bello; Abiola Ogundeji; Sun Yu; Xin Jiang; Liting Deng; Liyan Zhao; Chol Jong; Xiuhong Xu (Archives of Microbiology, 2022)

AFAP1-AS1: a rising star among oncogenic long non-coding RNAs - Fang Xiong; Kunjie Zhu; Su Deng; Hongbin Huang; Liting Yang; Zhaojian Gong; Lei Shi; Yi He; Yanyan Tang; Qianjin Liao; Jianjun Yu; Xiaoling Li; et al. (Science China Life Sciences, 2021)

Comparison of global and local gamma evaluation results using isodose levels - Liting Yu; Tanya Kairn; Jamie V. Trapp; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Effects of metal stabilizers on soil hydraulic characteristics and mobility of cadmium - Lirong Liu; Dinggui Luo; Lezhang Wei; Yu Liu; Sibin Huang; Liting Huang; Zhenyu Xie; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Science and Pollution Research, 2020)

Numerical Investigation of Sloshing in Rectangular Tank with Permeable Baffle - Liting Yu; Mi-An Xue; Aimeng Zhu (Journal of Marine Science and Engineering, 2020)
Violent sloshing induced by excitation with large amplitudes or resonant frequencies may result in structural damage of the liquid-tank or even the overturning of the liquid cargo transport system. Therefore, impermeable and permeable vertical baffles were investigated numerically to suppress sloshing. The numerical simulations were based on the finite element method and arbitrary Lagrangian–Eulerian (ALE) method. The numerical model was verified by the available experimental data, numerical results and linear theoretical results. Based on the study of the effects of impermeable baffle height, amplitude and frequency of excitation on sloshing, the effects of baffle permeability on sloshing were investigated. Importantly, a critical permeability coefficient that was most effective to suppress sloshing was found. In addition, the maximum flow velocities in the tank with a baffle of small permeability coefficient were smaller than those in the tank with an impermeable baffle. While, the maximum flow velocities under a baffle of large permeability coefficient were larger than those in the tank with an impermeable baffle. Vortices were observed in the whole region of the baffle, tank bottom, tank walls and the free surface in the tank with a permeable baffle.

Dexmedetomidine for prevention of propofol injection pain upon induction of anesthesia: a meta-analysis - Liting Ji; Weihua Sun; Yunping Lan; Changxing Xia; Gongmin Yu; Qinghua Wu; Shufen Yang; Xiaofeng Xu (European Journal of Clinical Pharmacology, 2020)

Characteristics of inverse gamma histograms - Liting Yu; Tanya Kairn; Jamie V. Trapp; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2020)

Fungal community succession under influence of biochar in cow manure composting - Xin Jiang; Liting Deng; Qingxin Meng; Yu Sun; Yue Han; Xiaotong Wu; Siyuan Sheng; Haifeng Zhu; Bello Ayodeji; Ugochi Uzoamaka Egbeagu; Xiuhong Xu (Environmental Science and Pollution Research, 2020)

In vitro antiviral activity of Griffithsin against porcine epidemic diarrhea virus - Lan Li; Xiaoming Yu; Haoming Zhang; Haiwei Cheng; Liting Hou; Qisheng Zheng; Jibo Hou (Virus Genes, 2019)

Bis(propyl)-cognitin Prevents β-amyloid-induced Memory Deficits as Well as Synaptic Formation and Plasticity Impairments via the Activation of PI3-K Pathway - Liting Jiang; Meng Huang; Shujun Xu; Yu Wang; Pengyuan An; Chenxi Feng; Xiaowei Chen; Xiaofei Wei; Yifan Han; Qinwen Wang (Molecular Neurobiology, 2016)

Transformer 2β (Tra2β/SFRS10) positively regulates the progression of NSCLC via promoting cell proliferation - Lili Ji; Tingting Ni; Yanbo Shen; Qun Xue; Yifei Liu; Buyou Chen; Xuefan Cui; Liting Lv; Xiafei Yu; Yuan Cui; Xiaoning Lu; Jie Chen; et al. (Journal of Molecular Histology, 2014)

A simple and efficient method to rescue very virulent infectious bursal disease virus using SPF chickens - Fei Yu; Xiaole Qi; Li Gao; Yongqiang Wang; Yulong Gao; Liting Qin; Honglei Gao; Xiaomei Wang (Archives of Virology, 2012)

Clinical Evaluation of Targeted Arterial Infusion of Verapamil in the Interventional Chemotherapy of Primary Hepatocellular Carcinoma - Jin Huang; Qiaohong Duan; Pingsheng Fan; Chushu Ji; Yuying Lv; Xinmin Lin; Liting Qian; Xiukun Yu (Cell Biochemistry and Biophysics, 2011)